Bone marrow‐derived multipotent mesenchymal stromal cells from horses after euthanasia. Issue 4 (12th September 2017) - Schröck, Carmen; Eydt, Carina; Geburek, Florian; Kaiser, Lena; Päbst, Felicitas; Burk, Janina; Pfarrer, Christiane; Staszyk, Carsten
Abstract: Allogeneic equine multipotent mesenchymal stromal cells (eMSCs) have been proposed for use in regenerative therapies in veterinary medicine. A source of allogeneic eMSCs might be the bone marrow from euthanized horses. The purpose of this study was to compare in vitro characteristics of equine bone marrow derived eMSC (eBM‐MSCs) from euthanized horses (eut‐MSCs) and from narcotized horses (nar‐MSCs). Eut‐MSCs and nar‐MSCs showed typical eMSC marker profiles (positive: CD44, CD90; negative: CD11a/CD18 and MHCII) and possessed tri‐lineage differentiation characteristics. Although CD105 and MHCI expression varied, no differences were detected between eut‐MSCs and nar‐MSCs. Proliferation characteristics did not differ between eut‐MSCs and nar‐MSCs, but age dependent decrease in proliferation and increase in MHCI expression was detected. These results suggest the possible use of eut‐MSCs for therapeutic applications and production of commercial available eBM‐MSC products. Abstract : In vitro characteristics of bone marrow derived equine multipotent mesenchymal stromal cells (eMSC) from euthanized horses and from anesthetized horses were compared. No significant differences concerning differentiation capacities, proliferative and self‐renewal potential and cell surface marker profiles were detected. The results suggest a possible use of eMSC from euthanized horses at least for experimental purposes.